Courtyards for consumption: Tourist constructions of authenticity in the commodified Chinese courtyard buildings - Wawan Destiawan; Djudjun Rusmiatmoko (The Journal of City: Branding and Authenticity, 2026)
Background: The interior courtyard is the organising socio-spatial core of Chinese and Chinese-Indonesian (Peranakan) domestic architecture, yet in heritage-tourism districts it is increasingly repackaged as a consumable attraction. In Semarang’s Chinatown (Pecinan), community-led tourism since 2006 and a municipal revitalisation programme launched in 2023 have accelerated the conversion of courtyard buildings into cafés, cultural venues, and visitor attractions. Drawing on the staged-authenticity debate and on recent studies of courtyard commodification in East Asian cities, this study examines how visitors construct, negotiate, and contest the authenticity of commodified courtyard spaces in Pecinan Semarang, and what their narratives imply for the district’s brand. Methods: A netnographic design analyses publicly available Google Maps reviews of three courtyard-based heritage venues: Tay Kak Sie Grand Temple, the Rasa Dharma hall of Boen Hian Tong, and Dharma Boutique Roastery, coded deductively against a framework that crosses objective, constructive, and existential authenticity with spatial, social, and symbolic dimensions of place, complemented by inductive open coding. Findings: Preliminary coding of a purposive sample of 32 reviews indicates that objective (age-based) judgements and commodification signals co-dominate (41% each), existential encounters follow (34%), and the courtyard itself is explicitly named in only 6% of reviews — consumed as café seating and event space but absent from visitors’ vocabulary. Commodification is narrated overwhelmingly as access rather than loss, except where consumption enters sacred space; an emergent code of everyday communal use marks the association hall as a living institution rather than an attraction. Conclusion: The study provisionally identifies the “consumed but unnamed” courtyard and everyday communal use as overlooked authenticity resources for heritage-district branding in island Southeast Asia. Novelty/Originality of this article: This study extends authenticity research by introducing the concept of the "consumed but unnamed" courtyard and demonstrating how everyday communal use functions as an overlooked authenticity resource that reshapes heritage branding in commodified courtyard spaces.